The effect of nutrition on tennis athlete performance: a systematic review - Sayuty, Yogi; Sabillah, Muhamad Ichsan; Hidayat, Rezha Arzhan; Sholichah , Ima Fitri (Medicni Perspektivi, 2026)
Nutrition is crucial in improving athlete performance, and research on the relationship between nutrition and sport continues to grow. This article aims to investigate nutrition's influence on tennis athletes' performance through a systematic review approach. The main objective was to identify the types of food that are most influential in improving the performance of tennis athletes, as well as to evaluate their impact on physiological and psychological aspects. This study used a systematic review approach, following PRISMA guidelines. Databases such as PubMed, Scopus, and Web of Science were reviewed for articles published up to 2024, using keywords related to nutrition and tennis. Inclusion and exclusion criteria were set to select articles that fit the research topic. Data were then extracted, synthesized, and analyzed to produce significant findings in the context of nutrition's influence on tennis athletes' performance. Of the 500 articles identified, 44 met the inclusion criteria. The analysis concluded that nutrition is essential in enhancing a tennis athlete's performance. Carbohydrates, protein, and fat were shown to be vital sources of energy for tennis athletes, while vitamins and minerals play an essential role in recovery and optimal body function. Previous studies have also shown that proper diet and supplementation can significantly improve tennis athletes' stamina, strength, and recovery. This study confirms that proper nutrition is highly influential in improving the performance of tennis athletes. Optimizing carbohydrate, protein, fat, vitamin, and mineral intake can have significant physiological and psychological benefits such as stamina, strength, and recovery. These findings result in recommendations for a tennis athlete's diet tailored to individual needs. At the same time, further research is recommended to deepen the understanding of the relationship between nutrition and sports performance.